The CTLA‐4 immune checkpoint protein regulates PD‐L1:PD‐1 interaction via transendocytosis of its ligand CD80. (2nd February 2023) - Kennedy, Alan; Robinson, Maximillian A; Hinze, Claudia; Waters, Erin; Williams, Cayman; Halliday, Neil; Dovedi, Simon; Sansom, David M
Abstract: CTLA‐4 and PD‐1 are key immune checkpoint receptors that are targeted in the treatment of cancer. A recently identified physical interaction between the respective ligands, CD80 and PD‐L1, has been shown to block PD‐L1/PD‐1 binding and to prevent PD‐L1 inhibitory functions. Since CTLA‐4 is known to capture and degrade its ligands via transendocytosis, we investigated the interplay between CD80 transendocytosis and CD80/PD‐L1 interaction. We find that transendocytosis of CD80 results in a time‐dependent recovery of PD‐L1 availability that correlates with CD80 removal. Moreover, CD80 transendocytosis is highly specific in that only CD80 is internalised, while its heterodimeric PD‐L1 partner remains on the plasma membrane of the antigen‐presenting cell (APC). CTLA‐4 interactions with CD80 do not appear to be inhibited by PD‐L1, but efficient removal of CD80 requires an intact CTLA‐4 cytoplasmic domain, distinguishing this process from more general trogocytosis and simple CTLA‐4 binding to CD80/PD‐L1 complexes. These data are consistent with CTLA‐4 acting as modulator of PD‐L1:PD‐1 interactions via control of CD80. Synopsis: The CTLA‐4 and PD‐1 immune checkpoint pathways intersect by cis interaction between their respective ligands (CD80 and PD‐L1), which interferes with PD‐L1 binding to PD‐1. Here, CTLA‐4‐mediated transendocytosis is shown to selectively deplete CD80 from the cell surface, resulting in the liberation of functional PD‐L1 that can interact with PD‐1. CD80 interacts with PD‐L1 to form cis heterodimers that prevent binding to PD‐1. CTLA‐4 transendocytosis removes CD80, but not PD‐L1, restoring the ability of PDL1 to bind PD‐1. Binding of CTLA‐4 in soluble or non‐endocytic forms to CD80‐PD‐L1 heterodimers does not effectively release free functional PD‐L1. CTLA‐4 can influence PD‐L1‐PD‐1 interaction and function by controlling CD80 expression. CTLA‐4 regulates PD‐L1‐PD‐1 interactions via transendocytosis of CD80. Abstract : CD80 removal via its cognate receptor CTLA‐4 disrupts CD80/PD‐L1 ligand complexes and frees PD‐L1 for PD‐1 binding and immune response suppression.